2019
DOI: 10.3390/medsci7040057
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Chronic Rhinosinusitis in Cystic Fibrosis

Abstract: Cystic fibrosis patients frequently develop chronic rhinosinusitis as a result of their propensity to form inspissated mucus and impairment of mucociliary clearance. They exhibit variable symptom burden even in the setting of positive radiographic and endoscopic findings. Current evidence suggests a positive effect of managing sinonasal disease on pulmonary health. Topical antimicrobial and mucolytic therapies are frequently required to manage the disease with surgery reserved for refractory cases. Endoscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…With respect to surgical technique, sinus hypoplasia and anatomic variants can make complete ESS difficult, which is especially important in CF as inspissated secretions may be trapped in partially removed partitions or unopened cells. Therefore, careful pre‐operative review of CT anatomy remains crucial 2397 . While extended surgical procedures such as endoscopic medial maxillectomy and Draf 3 procedures have shown favorable long‐term sinonasal outcomes, 1984,2398 comparative studies are lacking, and therefore should be considered on a case by case basis based on the degree of disease and mechanism of failure in the case of revision ESS.…”
Section: Special Considerations In Rhinosinusitismentioning
confidence: 99%
“…With respect to surgical technique, sinus hypoplasia and anatomic variants can make complete ESS difficult, which is especially important in CF as inspissated secretions may be trapped in partially removed partitions or unopened cells. Therefore, careful pre‐operative review of CT anatomy remains crucial 2397 . While extended surgical procedures such as endoscopic medial maxillectomy and Draf 3 procedures have shown favorable long‐term sinonasal outcomes, 1984,2398 comparative studies are lacking, and therefore should be considered on a case by case basis based on the degree of disease and mechanism of failure in the case of revision ESS.…”
Section: Special Considerations In Rhinosinusitismentioning
confidence: 99%
“…This difference may in part be related to the higher rates of aplastic frontal sinuses in patients with CF Moreover, the higher rates of maxillary sinus revisions appear consistent with recommendations in the literature to perform large maxillary antrostomies in patients with CF in order to prevent poor mucociliary clearance in this cohort. 26,27 Overall, revision rates for every sinus were higher among patients with CF compared to those without CF It is important to acknowledge that the data presented herein is prior to the emergence of HEMT. Today, the majority of patients with CF are eligible for these therapies.…”
Section: Discussionmentioning
confidence: 91%
“…Genotype appears to impact both sinonasal development and CRS severity, 10 and CF patients can be classified into low‐risk (IV‐V) and high‐risk (I‐III) classes based on different CFTR mutations 11 . Endoscopic sinus surgery (ESS) is widely accepted as the standard of care after the failure of adequate medical treatment with some authors supporting upfront “extended” ESS (e.g., modified medial maxillectomy/MEMM, Draf III procedures) in these patients 12,13 . However, ESS is associated with a potential risk of serious complications that occur in about 0.5% to 1% of non‐CF patients, 14 and it was shown that preoperative CT imaging is able to identify anatomical variants at risk for their occurrence 15–17 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Endoscopic sinus surgery (ESS) is widely accepted as the standard of care after the failure of adequate medical treatment with some authors supporting upfront "extended" ESS (e.g., modified medial maxillectomy/MEMM, Draf III procedures) in these patients. 12,13 However, ESS is associated with a potential risk of serious complications that occur in about 0.5% to 1% of non-CF patients, 14 and it was shown that preoperative CT imaging is able to identify anatomical variants at risk for their occurrence. [15][16][17] Despite many reports studied CF-related CRS and the relationships between genetic mutations and sinonasal development, 8,[18][19][20][21][22] how these anatomical variants influence the operative risk is unclear.…”
Section: Introductionmentioning
confidence: 99%